Sprint running: a new energetic approach - Di Prampero, P. E.; Fusi, S.; Sepulcri, L.; Morin, J.-B.; Belli, A.; Antonutto, G. (The Journal of Experimental Biology, 2005)
The speed of the initial 30 m of an all-out run from a stationary start on a flat track was determined for 12 medium level male sprinters by means of a radar device. The peak speed of 9.46±0.19 m s-1 (mean ± S.D.) was attained after about 5 s, the highest forward acceleration (af), attained immediately after the start, amounting to 6.42±0.61 m s-2. During acceleration, the runner's body (assumed to coincide with the segment joining the centre of mass and the point of contact foot terrain) must lean forward, as compared to constant speed running, by an angle =arctang/af (g=acceleration of gravity). The complement (90-) is the angle, with respect to the horizontal, by which the terrain should be tilted upwards to bring the runner's body to a position identical to that of constant speed running. Therefore, accelerated running is similar to running at constant speed up an `equivalent slope' ES=tan(90-). Maximum ES was 0.643±0.059. Knowledge of ES allowed us to estimate the energy cost of sprint running (Csr, J kg-1 m-1) from literature data on the energy cost measured during uphill running at constant speed. Peak Csr was 43.8±10.4 J kg-1 m-1; its average over the acceleration phase (30 m) was 10.7±0.59 J kg-1 m-1, as compared with 3.8 for running at constant speed on flat terrain. The corresponding metabolic powers (in W kg-1) amounted to 91.9±20.5 (peak) and 61.0±4.7 (mean).